MiR-125a-3p-KLF15-BCAA Regulates the Skeletal Muscle Branched-Chain Amino Acid Metabolism in Nile Tilapia (Oreochromis niloticus) During Starvation - Li, Honghui; An, Xiaoling; Bao, Lingsheng; Li, Yulong; Pan, Yaxiong; He, Jinggang; Liu, Li; Zhu, Xin; Zhang, Jianshe; Cheng, Jia; Chu, Wuying (Frontiers in Genetics, 2020)
The branched-chain amino acids (BCAA) play an important role as the energy metabolism of muscle, and Krüppel-like factor 15 (KLF15) as a transcription factor which critical regulator of BCAA metabolism in the skeletal muscle. In this study, we assessed the effect of starvation for 0, 3, 7, 15 days on BCAA metabolism in skeletal muscle of Nile tilapia. The results showed that the expression of KLF15 was increased first and then decreased during starvation, as well as the expression and activity of branched-chain aminotransferase 2 (BCAT2) and alanine aminotransferase (ALT). On the other hand, the content of BCAA was a first decreased and then up-regulated, and reached the lowest level after 3 days of starvation. In addition, through dual-luciferase reporter assay and injection experiments, it was found that KLF15 is the target gene of miR-125a-3p, which further verified that miR-125a-3p can regulate the BCAA metabolism by targeting KLF15 in the skeletal muscle. Thus, our work investigated the possible mechanisms of BCAA metabolism adapting to nutritional deficiency in skeletal muscle of Nile tilapia, and illustrated the regulation of branched-chain amino acids metabolism through miR-125a-3p-KLF15-BCAA pathway in the skeletal muscle.